KLONING MANUSIA:SEBUAH DILEMA - Widodo, Wahyu (Jurnal Bestari, 2003)
Cloning is the production of one or more individual plants or animals or humans that are genetically identical to another plant or animal or human.There are three different types of ?cloning? are: embryo cloning,adult DNA cloning and therapeutic cloning.Some scientists believe that human cloning is moral and might eventually lead to very positive result,such as for cure,help parent infertil and produce a reservoir of ?organ spare parts?. In the other hand,some individuals and groups have expressed concern about adverse effect of human cloning,and question its morality.One of their reason is a fertilized ovum is a full human person.Whent its nucleus is removed during cloning,that person is,in effect,murdered.Member of some religious groups,particularry evangelical Christianity and Roman Catholicism,believe that a soul enters the body at the instant of conception,and that the fertilized ovum is in fact a human person with full human right.Dividing that ?baby? in half during an human cloning procedure would interfere with God?s intent.It is also human experimentation on live person.The many cloned zigotes that died after a few ceel divisions would be lost human beings;their loss is considered as serious as the death of new born baby.In Islam,there is now central authority comparable to the pope in Roman Catholicism.There are a lot of arguments,but almost said if the extension of cloning to human beings would create extremely complex and intractable social and moral problems.